THE ROLE OF SELF-EMPLOYMENT IN EFFECTIVELY REDUCING INFORMAL EMPLOYMENT - Tagaev Behzod Ergashevich; Chinorova Shahodat Mansur qizi (MANAGEMENT AND ECONOMICS SCIENTIFIC RESEARCH JOURNAL, 2025)
Nowadays, the share of the informal sector is much higher in developin countries compared to developes ones. There are several effective ways to reduce the number of people working in the informal sector, and one of them is self-employment. In Uzbekistan today, many opportunities are being created for self-employed people. This article looks at self-employment as an important step in reducing informal employment and making it more beneficial for both society and the state.